REFRAMING PHILANTHROPY: STAKEHOLDER COLLABORATION AND THE ECOLOGY OF SUSTAINABLE DEVELOPMENT - Eko Muliansyah; Muh Gani Irwansyah (PT. Jurnal Center Indonesia Publisher, 2026)
Philanthropy has increasingly evolved from a form of charitable assistance into a strategic actor within sustainable development processes. However, much of the existing practice and literature still treats philanthropy as an isolated or supplementary intervention, limiting its potential to generate systemic and long-term impact. This article aims to critically examine the role of philanthropic institutions within a broader ecosystem of sustainable development, emphasizing the importance of multi-stakeholder collaboration involving government, the private sector, academia, and local communities. Using a qualitative literature review with a conceptual and analytical orientation, this study synthesizes scholarly works on philanthropy, collaborative governance, corporate social responsibility, Islamic philanthropy, and the Sustainable Development Goals (SDGs), with a particular focus on Indonesia and the Global South. The analysis demonstrates that philanthropic contributions become more effective and sustainable when embedded within an integrated development ecology, rather than operating through fragmented and project-based approaches. The findings highlight philanthropy’s strategic roles as a catalyst for social innovation, a bridge between sectors, and a facilitator of long-term social investment. Islamic philanthropic instruments such as zakat and productive waqf further illustrate how value-based financial mechanisms can support inclusive development when professionally managed and aligned with national and global development agendas. This study contributes conceptually by reframing philanthropy as a system-level change agent within a sustainable development ecology, offering an integrative lens for understanding collaboration, governance, and impact. The article concludes that sustainable development is best achieved not through isolated institutional efforts, but through coordinated, trust-based ecosystems in which philanthropy plays a transformative and connective role.